The Human Rights Act, asylum, and the campaign against Section 55 - Sharma, P (2010)
A major objective of the Human Rights Act (HRA) was to bring about a culture of rights in the UK. Its introduction fore-grounded questions about the use of rights to advance social justice issues and was the impetus for this research. At about the same as the Act came into effect another law, Section 55, an antithesis of what the HRA promised, was passed which forced thousands of asylum-seekers into destitution. Section 55 became a major battleground pitting non-governmental organisations (NGOs) against the Home Office in a three-year long campaign, characterised by rancour and viciousness, unlike any in recent memory. The NGOs, with the new HRA as a key part of their strategy, defeated the legislation. This thesis, a bottom-up case study of rights at work, examines the role of rights in the campaign to assess (1) if rights brought about social changes and (2) is a culture of rights developing in the UK? The paper first considers the various theoretical frameworks on rights and social change and analyses various case studies of rights at work. Context is important; therefore, it also examines how asylum has come to be framed in present-day discourse, with an overview on the evolution of welfare as a coercive measure. The study, framed against current events of the day, concludes that while test-case challenges eventually defeated Section 55 welfare as a coercive measure continues. In short, the HRA has proven to be ineffective against illiberal policies and the development of a culture of rights, insofar as asylum is concerned, has stalled. And it has happened with deliberation by a government determined to be tough on asylum irrespective of the HRA.